Surface modification of natural polymers to impart low water absorbency - Thakur, V. K. (2013)
In the present work, graft copolymerization of ethyl acrylate (EA) onto mercerized natural cellulosic polymers in air in the presence of potassium persulfate (KPS) as initiator to impart low water absorbency is reported. Synthesized cellulose graft copolymers were characterized with FT-IR spectrophotometry, scanning electron microscopy (SEM), and thermal analysis TGA/DTA techniques. Thermal stability of natural polymer-g-poly (EA) was found to be more than that of raw and mercerized cellulosic polymers. On grafting, the graft copolymers were also found to exhibit more moisture, chemical, and thermal resistance.